2014
DOI: 10.1007/s10936-014-9323-5
|View full text |Cite
|
Sign up to set email alerts
|

Context, Contrast, and Tone of Voice in Auditory Sarcasm Perception

Abstract: Four experiments were conducted to investigate the interplay between context and tone of voice in the perception of sarcasm. These experiments emphasized the role of contrast effects in sarcasm perception exclusively by means of auditory stimuli whereas most past research has relied on written material. In all experiments, a positive or negative computer-generated context spoken in a flat emotional tone was followed by a literally positive statement spoken in a sincere or sarcastic tone of voice. Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
3
13
0
Order By: Relevance
“…Our results pointed out the general impact of prosody in the subgroup named PROSODY+ compared to the subgroup named PROSODY-, meaning that the PROSODY+ subgroup judged the statements to be more ironic when uttered with an ironic prosody compared to statements spoken with a neutral prosody, specifically in the weak incongruity and no incongruity context conditions whereas this was not the case for the PROSODYsubgroup. The results obtained in the PROSODY+ subgroup were consistent with those in the second experiment of Voyer et al (2014). Thus, we confirm that ironic prosody can be a reliable cue for irony understanding (Cheang and Pell, 2008;Voyer et al, 2014;Peters et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Our results pointed out the general impact of prosody in the subgroup named PROSODY+ compared to the subgroup named PROSODY-, meaning that the PROSODY+ subgroup judged the statements to be more ironic when uttered with an ironic prosody compared to statements spoken with a neutral prosody, specifically in the weak incongruity and no incongruity context conditions whereas this was not the case for the PROSODYsubgroup. The results obtained in the PROSODY+ subgroup were consistent with those in the second experiment of Voyer et al (2014). Thus, we confirm that ironic prosody can be a reliable cue for irony understanding (Cheang and Pell, 2008;Voyer et al, 2014;Peters et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
“…Developing different experiments in English, Voyer et al (2014) found a strong interaction between context and prosody, concluding that prosody contributes to emphasizing the contrast effect in sarcasm perception. They manipulated the level of incongruity between the context and the speaker's utterance using three types of context (i.e., a positive context with no contextual incongruity leading to sincerity, a negative context with a strong contextual incongruity leading to sarcasm, an ambiguous context with a weak contextual incongruity) (Voyer et al, 2014). Their results revealed that the proportion of sarcastic responses in ambiguous contexts remained within the proportions obtained for congruent context-prosody pairs (e.g., negative context matched with sarcastic prosody and positive context matched with sincere prosody) and the incongruent pairs in the direction predicted by the prosody.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations